Appréhender la banlieue: Les Passagers du Roissy-Express et l'exploration spatiale - Edward Welch (Francosphères)
In May 1989, François Maspero and Anaïk Frantz undertook a journey along the RER B between Roissy airport and St Rémy-lès-Chevreuse, which formed the basis of their book Les Passagers du Roissy-Express (1990). The text would become a key landmark for thinking about urban space in contemporary France, its exploration and portrayal. Twenty-five years on, what does it have to tell us about the nature and possibilities of spatial enquiry? What can we learn from it about apprehending the spaces of the banlieue? Does it remain a reliable guide to the locations it describes? This article sets out to review the emblematic status acquired by Les Passagers du Roissy-Express since 1990. Resituating the text in the broader context of a preoccupation with space in contemporary French culture, it highlights in particular its reflections on the passage of space through time, and the palimpsestual layering of history in place that occurs as a result. It also considers the text's articulation of a phenomenologically-based mode of spatial enquiry grounded in walking and image-making.